Implementasi Akad Tijarah dan Akad Tabarru’ Pada Asuransi Syariah - M. Akbar Nafa; Jefik Zulfikar Hafizd; Asep Saepullah; Abdul Fatakh; Ahmad Khoirudin (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
This study aims to analyze the implementation of tijarah and tabarru’ contracts at PT Asuransi Jiwa Syariah Al-Amin in Cirebon and assess their conformity with Islamic economic law. It employs a qualitative method with an empirical juridical approach. Primary data were collected through interviews with the branch manager and marketing staff, observation, and documentation of insurance policies, application forms, product provisions, and fund-management mechanisms. Secondary data were drawn from DSN-MUI fatwas, regulations, books, and relevant scholarly articles, then analyzed descriptively through data reduction, presentation, interpretation, and conclusion drawing. The findings show that the tijarah contract is implemented through wakālah bi al-ujrah, under which participants authorize the company to manage their funds in return for an ujrah. The tabarru’ contract is implemented through participants’ charitable contributions placed in a separate account for claim payments and mutual protection. These practices generally satisfy the principles of contractual clarity, fund segregation, transparency, justice, and mutual assistance and refer to DSN-MUI Fatwa No. 52/2006 and No. 53/2006. The study concludes that the integration of both contracts is consistent with Islamic economic law, although transparency in ujrah determination and tabarru’ fund management requires stronger oversight.